Rescue of synthetic analogs of respiratory syncytial virus genomic RNA and effect of truncations and mutations on the expression of a foreign reporter gene. - Collins, P L (1991)
The viral genomic RNA (vRNA) of human respiratory syncytial virus is a nonsegmented negative strand that is not infectious alone. To develop methods for complementing synthetic vRNA with viral proteins, a cDNA was constructed to encode a vRNA in which all of the viral protein-coding sequences were removed and replaced with a negative-sense copy of the bacterial chloramphenicol acetyltransferase gene. Upon transfection into respiratory syncytial virus-infected cells, the synthetic vRNA was "rescued" such that it was amplified, expressed, and packaged into infectious virions. A heterologous paramyxovirus, parainfluenza virus 3, was inactive in rescue. Further internal deletions mapped the cis-acting viral sequences required for rescue to two segments totaling 105 nucleotides (nt) derived from the two vRNA ends. Rescue was unaffected by replacement of the 44-nt 3'-terminal leader region with a 50-nt sequence that is complementary to the 5' terminus and represents the 3' end of the positive-sense replicative intermediate RNA. This 5'-end complement was related to the parental leader region only near the 3' terminus (91% or 73% identical for the first 11 or 22 nt, respectively). The addition of 11 heterologous nt to the 3' end of the parental leader region ablated rescue, suggesting that the 3'-proximal conserved domain is required and cannot function from an internal site. However, deletion of the 3'-terminal 3 nt, or a double transition at positions 4 and 5, had no effect on rescue. Thus, the 3'-terminal 5 nt, although conserved between 3' ends of the negative- and positive-sense RNAs, do not appear to be essential.